Study on digital visual support intervention: a review of the influence of engagement and motivation on students with autism - Anblagan, Tharishni; Ahmad, Nor Aniza; Roslan, Samsilah (Human Resource Management Academic Research Society, 2023)
Technology has been receiving much attention in special education, resulting in visual support being used as an intervention tool among students with autism spectrum disorder. A digital visual support intervention is introduced as a visual representation to aid independence when completing a series of tasks. Students’ motivation and engagement during the task are further examined during the task. This paper proposes a review of the influence of engagement and motivation on digital visual support interventions. The researcher will employ Design and Development Research (DDR) with three respective phases: a) Need Analysis Phase; b) Design and Development Phase; and c) Evaluation Phase. The expected outcome of this study will benefit the autism students, educators, researchers, and policymakers for future research in the field of special education intervention.